Evaluation of otorhinolaryngological manifestations in patients with primary ciliary dyskinesia. (May 2023) - Günaydın, Rıza Önder; Eroğlu, Ergin; Tellioğlu, Burçay; Emiralioğlu, Nagehan; Özçelik, Hayriye Uğur; Yalçın, Ebru; Doğru, Deniz; Kiper, Emine Nural
Abstract: Objectives: Primary ciliary dyskinesia (PCD) is a genetic disease characterized by congenital impairment of mucociliary clearance causing recurrent respiratory tract infections. Pulmonary manifestations of PCD are well-known whereas adequate data on otorhinolaryngological complications is lacking. The aim of this study was to investigate clinical features, course and related factors of otorhinolaryngologic domains in PCD patients. Methods: Patients with a diagnosis of PCD who were on follow-up in the ear-nose-throat (ENT) department of our center between 2000 and 2021 were enrolled. Demographic and clinical data, frequency of sinonasal and otological complaints, examination findings and possible risk factors associated with otorhinolaryngological diseases were obtained via electronic medical charts retrospectively. Results: Of the 121 patients, 53% were male, median age at PCD diagnosis was 7 years (1 month - 20 yrs). The most common ENT manifestation was otitis media with effusion (OME) (66.1%, n = 80), followed by acute otitis media (43.8%, n = 53), acute rhinosinusitis (ARS) (28.9%, n = 35), chronic rhinosinusitis (CRS) (27.3%, n = 33) and chronic otitis media (10.7%, n = 13). Patients with ARS and CRS were significantly older than patients who did not have ARS and CRS (p = 0.045 and p = 0.028, respectively). The annual number of ARS attacks also correlated with age of patients positively (r = 0.170, p = 0.06). Of the 45 patients with pure-tone audiometry, most common finding was conductive hearing loss (CHL) in 57, 8% (n = 26). Presence of OME significantly increased tympanic membrane injury which was observed as sclerosis, perforation, retraction or changes due to ventilation tube insertion (VTI). (OR: 8.6, 95% CI: 3.6–20.3, p < 0.001). Conclusions: Otorhinolaryngologic diseases are common, variable and complicated in PCD patients, consequently ENT physicians' awareness should be improved through shared experiences. ARS and CRS seem to appear in older PCD patients. Presence of OME is the most important risk factor for tympanic membrane damage. Highlights: Primary ciliary dyskinesia (PCD) is a rare genetic disease with associating otorhinolaryngological manifestations including recurring rhinosinusitis and otitis media. Otitis media with effusion is the most common otologic finding causing conductive hearing loss in PCD. There is a need for diagnostic and etiologic approach for PCD patients reporting balance problems.